Morphological variation in Homo erectus and the origins of developmental plasticity - Antón, Susan C. (Philos Trans R Soc Lond B Biol Sci, 2016)
Homo erectus was the first hominin to exhibit extensive range expansion. This extraordinary departure from Africa, especially into more temperate climates of Eurasia, has been variously related to technological, energetic and foraging shifts. The temporal and regional anatomical variation in H. erectus suggests that a high level of developmental plasticity, a key factor in the ability of H. sapiens to occupy a variety of habitats, may also have been present in H. erectus. Developmental plasticity, the ability to modify development in response to environmental conditions, results in differences in size, shape and dimorphism across populations that relate in part to levels of resource sufficiency and extrinsic mortality. These differences predict not only regional variations but also overall smaller adult sizes and lower levels of dimorphism in instances of resource scarcity and high predator load. We consider the metric variation in 35 human and non-human primate ‘populations’ from known environmental contexts and 14 time- and space-restricted paleodemes of H. erectus and other fossil Homo. Human and non-human primates exhibit more similar patterns of variation than expected, with plasticity evident, but in differing patterns by sex across populations. The fossil samples show less evidence of variation than expected, although H. erectus varies more than Neandertals. This article is part of the themed issue ‘Major transitions in human evolution’.